Importance of deep mixing and silicic acid in regulating phytoplankton biomass and community in the iron-limited Antarctic Polar Front region in summer. (April 2017) - Cheah, Wee; Soppa, Mariana A.; Wiegmann, Sonja; Ossebaar, Sharyn; Laglera, Luis M.; Strass, Volker H.; Santos-Echeandía, Juan; Hoppema, Mario; Wolf-Gladrow, Dieter; Bracher, Astrid
Abstract: Phytoplankton community structure and their physiological response in the vicinity of the Antarctic Polar Front (APF; 44°S to 53°S, centred at 10°E) were investigated as part of the ANT-XXVIII/3 Eddy-Pump cruise conducted in austral summer 2012. Our results show that under iron-limited ( < 0.3 μ mol m − 3 ) conditions, high total chlorophyll-a (TChl-a) concentrations ( > 0.6 mg m − 3 ) can be observed at stations with deep mixed layer ( > 60 m ) across the APF. In contrast, light was excessive at stations with shallower mixed layer and phytoplankton were producing higher amounts of photoprotective pigments, diadinoxanthin (DD) and diatoxanthin (DT), at the expense of TChl-a, resulting in higher ratios of (DD+DT)/TChl-a. North of the APF, significantly lower silicic acid (Si(OH)4 ) concentrations ( < 2 mmol m − 3 ) lead to the domination of nanophytoplankton consisting mostly of haptophytes, which produced higher ratios of (DD+DT)/TChl-a under relatively low irradiance conditions. The Si(OH)4 replete ( > 5 mmol m − 3 ) region south of the APF, on the contrary, was dominated by microphytoplankton (diatoms and dinoflagellates) with lower ratios of (DD+DT)/TChl-a, despite having been exposed to higher levels of irradiance. The significant correlation between nanophytoplankton and (DD+DT)/TChl-a indicates that differences in taxon-specific response to light are also influencing TChl-a concentration in the APF during summer. Our results reveal that provided mixing is deep and Si(OH)4 is replete, TChl-a concentrations higher than 0.6 mg m − 3 are achievable in the iron-limited APF waters during summer.